Correlation between Phenylphenalenone Phytoalexins and Phytopathological Properties in Musa and the Role of a Dihydrophenylphenalene Triol (2002)
ABSTRACT: A correlation has been established between production of specific phenylphenalenones and resistance of various banana and plantain varieties towards certain pathogens. In addition a dihydrotrihydroxyphenylphenalene was isolated from the resistant 'Pelipita' plantain variety in relatively high concentrations and its structure and relative configuration were assigned on the basis of 1D and 2D NMR and NOE information. This compound is considered a key intermediate in the biosynthesis of phenylphenalenone phytoalexins.